2022
DOI: 10.3390/life12010099
|View full text |Cite
|
Sign up to set email alerts
|

Early Biomarkers Associated with P53 Signaling for Acute Radiation Injury

Abstract: Accurate dose assessment within 1 day or even 12 h after exposure through current methods of dose estimation remains a challenge, in response to a large number of casualties caused by nuclear or radiation accidents. P53 signaling pathway plays an important role in DNA damage repair and cell apoptosis induced by ionizing radiation. The changes of radiation-induced P53 related genes in the early stage of ionizing radiation should compensate for the deficiency of lymphocyte decline and γ-H2AX analysis as novel bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Particularly, gamma-glutamyl transferase 1 [GGT1], Phospholipase A2G [PLA2], post-transcriptional gene silencing [PTGS], glutathione peroxidase 6 [GPX6], aldolase, fructose-bisphosphate A [ALDOA], acyl-CoA synthetase short chain family member 2 [ACSS2], aldehyde dehydrogenase 3 family member A1 [ALDH3A1], and gamma-glutamyl transferase 6 [GGT6], involved in nitrogen metabolism, glutathione metabolism, glycolysis, or glycogenesis, and arachidonic acid metabolism, were suggested to be regulated by p53 [ 211 ]. DDB2, AEN, TP53 regulated inhibitor of apoptosis (TRIAP1), and TRAF4, which are all downstream of p53, are potential biomarkers within the first 24 h after radiation exposure [ 214 ].…”
Section: P53 As a Biomarker After Irradiationmentioning
confidence: 99%
“…Particularly, gamma-glutamyl transferase 1 [GGT1], Phospholipase A2G [PLA2], post-transcriptional gene silencing [PTGS], glutathione peroxidase 6 [GPX6], aldolase, fructose-bisphosphate A [ALDOA], acyl-CoA synthetase short chain family member 2 [ACSS2], aldehyde dehydrogenase 3 family member A1 [ALDH3A1], and gamma-glutamyl transferase 6 [GGT6], involved in nitrogen metabolism, glutathione metabolism, glycolysis, or glycogenesis, and arachidonic acid metabolism, were suggested to be regulated by p53 [ 211 ]. DDB2, AEN, TP53 regulated inhibitor of apoptosis (TRIAP1), and TRAF4, which are all downstream of p53, are potential biomarkers within the first 24 h after radiation exposure [ 214 ].…”
Section: P53 As a Biomarker After Irradiationmentioning
confidence: 99%
“…Therefore, Repairable DNA damage is normally transient, whereas P53 activation causes cells to initiate an apoptotic pathway (Ragunathan et al, 2020). Another study reported that P53 can be use as biodosimitry marker to demonstrate the radiosensitivity in early exposure within 24 h after IR exposure (Li et al, 2022). P53 is an important tumor suppressor gene that is expressed at low levels in cells, when cells are exposed to stress-induced stimulation, the expression of p53 increases, preventing genome destruction, which assist in maintaining cell stability and preventing cancer development (Kong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the integration of data from multiple cohorts is essential to generate robust and reproducible results (Beuchel et al, 2021). Here, we detected 20 radio-responsive genes and 17 of these 20 genes (i.e., APOBEC3H, ASCC3, DDB2, E2F7, FDXR, FHL2, GADD45, LIG1, MDM2, PCNA, PHPT1, POLH, RPS27L, SLC4A11, TNFSF4, VWCE, and ZNF79) have been previously identified as IR responsive genes (Kang et al, 2003;Dressman et al, 2007;Fachin et al, 2007;Gruel et al, 2008;Meadows et al, 2008;Paul and Amundson, 2008;Henríquez Hernández et al, 2009;Kabacik et al, 2011;Mayer et al, 2011;Pogosova-Agadjanyan et al, 2011;Templin et al, 2011;Wen et al, 2011;Boldt et al, 2012;Knops et al, 2012;El-Saghire et al, 2013;Nosel et al, 2013;Paul et al, 2013;Versteyhe et al, 2013;Beer et al, 2014;Vinoth et al, 2014;Ghandhi et al, 2015;Macaeva et al, 2016;Rouchka et al, 2016;Broustas et al, 2017;Lacombe et al, 2018;Piotto et al, 2018;Ghandhi et al, 2019;Cruz-Garcia et al, 2020a;Cruz-Garcia et al, 2020b;Li et al, 2022). Two of the three remaining DEGs (i.e., CCL27 and GLS2) have also been described in the context of DNA damage or of oxidative stress, which is also related to radiation as radiationinduced reactive oxygen species (ROS).…”
Section: Figurementioning
confidence: 92%